Interleukin-2 signalling is modulated by a labile disulfide bond in the CD132 chain of its receptor. Issue 1 (January 2012) - Metcalfe, Clive; Cresswell, Peter; Barclay, A. Neil
Abstract : Certain disulfide bonds present in leucocyte membrane proteins are labile and can be reduced in inflammation. This can cause structural changes that result in downstream functional effects, for example, in integrin activation. Recent studies have shown that a wide range of membrane proteins have labile disulfide bonds including CD132, the common gamma chain of the receptors for several cytokines including interleukin-2 and interleukin-4 (IL-2 and IL-4). The Cys 183 –Cys 232 disulfide bond in mouse CD132 is susceptible to reduction by enzymes such as thioredoxin (TRX), gamma interferon-inducible lysosomal thiolreductase and protein disulfide isomerase, which are commonly secreted during immune activation. The Cys 183 –Cys 232 disulfide bond is also reduced in an in vivo lipopolysaccharide (LPS)-induced acute model of inflammation. Conditions that lead to the reduction of the Cys 183 –Cys 232 disulfide bond in CD132 inhibit proliferation of an IL-2-dependent T cell clone and concomitant inhibition of the STAT-5 signalling pathway. The same reducing conditions had no effect on the proliferation of an IL-2-independent T cell clone, nor did they reduce disulfide bonds in IL-2 itself. We postulate that reduction of the Cys 183 –Cys 232 disulfide in CD132 inhibits IL-2 binding to the receptor complex. Published data show that the Cys 183 –Cys 232 disulfide bond is exposed at the surface of CD132 and in close contact with IL-2 and IL-4 in their respective receptor complexes. In addition, mutants in these Cys residues in human CD132 lead to immunodeficiency and loss of IL-2 binding. These results have wider implications for the regulation of cytokine receptors in general, as their activity can be modulated by a 'redox regulator' mechanism caused by the changes in the redox environment that occur during inflammation and activation of the immune system.